Rilzabrutinib, a reversible covalent Bruton's tyrosine kinase inhibitor: Absorption, metabolism, excretion, and absolute bioavailability in healthy participants - Sibel Ucpinar; Patrick F. Smith; Li Long; Fujun Li; Hui Yan; Jyoti Wadhwa; Katherine A. Chu; Jin Shu; Philip Nunn; Mengyao Li (Wiley, 2023)
Abstract This single‐center, open‐label, non‐randomized, two‐part, phase I study was conducted (1) to evaluate the absolute oral bioavailability of rilzabrutinib 400 mg tablet following an i.v. microtracer dose of ~100 μg [14C]‐rilzabrutinib (~1 μCi) and single oral dose of 400 mg rilzabrutinib tablet (part 1), and (2) to characterize the absorption, metabolism, and excretion (AME) of 14C‐radiolabeled rilzabrutinib following single oral dose (300 mg) of [14C]‐rilzabrutinib (~1000 μCi; administered as a liquid) in healthy male participants (part 2). A total of 18 subjects were enrolled (n = 8 in part 1; n = 10 in part 2). The absolute bioavailability of 400 mg rilzabrutinib oral tablet was low (<5%). In part 1, rilzabrutinib was absorbed rapidly after single oral dose of rilzabrutinib 400 mg tablet with a median (range) time to maximum concentration (Tmax) value of 2.03 h (1.83-2.50 h). The geometric mean (coefficient of variation) terminal half‐life following the oral dose and i.v. microtracer dose of ~100 μg [14C]‐rilzabrutinib, were 3.20 (51.0%) and 1.78 (37.6%) h, respectively. In part 2, rilzabrutinib was also absorbed rapidly following single oral dose of 300 mg [14C]‐rilzabrutinib solution with a median (range) Tmax value of 1.00 h (1.00-2.00 h). The majority of total radioactivity was in the feces for both non‐bile collection subjects (92.9%) and bile collection subjects (87.6%), and ~5% of radioactivity was recovered in urine after oral administration. Urinary excretion of unchanged rilzabrutinib was low (3.02%). The results of this study advance the understanding of the absolute bioavailability and AME of rilzabrutinib and can help inform its further investigation.